ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN DI PROVINSI JAWA TIMUR - Saputro, Rudi; Soelistyo, Aries (Jurnal Ekonomi Pembangunan, 2009)
The suggestion can be given relate to the finding obtained by during executing the research is: (1) With growth of high economics will be able to create opportunity of new job and unemployment can be permeated. the Unemployment amount decreasing hence unemployment storey;level will downhill also, (2) Government as taker of policy in the case of determination of minimum wage shall see do needed to take policy boost up the fee for the shake of prosperity of worker or don't boost up the governmental minimum wage can take correct policy so that worker good and entrepreneur is nothing that harmed, (3) Very relevant and complex Unemployment problem many matters, for that require to the existence of an sinergi and also cooperation from various side start dai governmental, private sector, society and individual to overcome the unemployment storey level increasing.